MENINGKATKAN KETERAMPILAN MEMBACA AL-QUR’AN DENGAN METODE TALAQQI PADA SISWA SEKOLAH DASAR DI UPTD SPF SDN MANDUMPANG KABUPATEN ACEH SINGKIL - Eliati Eliati; Maharaja Maharaja (lembaga Sepercenter, 2024)
Reading the Qur'an properly and correctly is a fundamental skill that every Muslim must master from an early age. However, many elementary school students still have difficulty in reading the Qur'an with fluency and eloquence. This study aims to improve the Qur'an reading skills of students at the Mandumpang Elementary School by applying the talaqqi method. The research method used is classroom action research (CAR) with two cycles. The research subjects are students in (specify the grade) with a total of (number of students). Data collection techniques were carried out through observation, interviews, and Qur'an reading tests. The results showed that the talaqi method was able to significantly improve students' Qur'an reading skills. In the first cycle, the percentage of students who read well reached (state the percentage), and increased to (state the percentage) in the second cycle. Thus, the talaqqi method can be used as an effective approach in learning to read the Qur'an at the elementary school level.